UNIVERSITY OF GEORGIA ROUNDTABLE ON: Enterprise‐Wide Risk Management. Issue 1 (23rd March 2020) - Verbrugge, James; Niehaus, Greg; Coleman, Walter; Lawder, Keith; Smith, Cliff; Briscoe, Christie; Ramamurtie, Sailesh; Chew, Don
Abstract : For many years, MBA students were taught that there was no good reason for companies that hedge large currency or commodity price exposures to have lower costs of capital, or trade at higher P/E multiples, than comparable companies that choose not to hedge such financial price risks. Corporate stockholders, just by holding well‐diversified portfolios, were said to neutralize any effects of currency and commodity price risks on corporate values. And corporate efforts to manage such risks were accordingly viewed as redundant, a waste of corporate resources on a function already performed by investors at far lower cost. But as this discussion makes clear, both the theory and the corporate practice of risk management have moved well beyond this perfect markets framework. The academics and practitioners in this roundtable begin by suggesting that the most important reason to hedge financial risks—and risk management's largest potential contribution to firm value—is to ensure a company's ability to carry out its strategic plan and investment policy. As one widely cited example, Merck's use of FX options to hedge the currency risk associated with its overseas revenues is viewed as limiting management's temptation to cut R&D in response to large currency‐related shortfalls in reported earnings. Nevertheless, one of the clear messages of the roundtable is that effective risk management has little to do with earnings management per se, and that companies that view risk management as primarily a tool for smoothing reported earnings have lost sight of its real economic function: maintaining access to low‐cost capital to fund long‐run investment. And a number of the panelists pointed out that a well‐executed risk management policy can be used to increase corporate debt capacity and, in so doing, reduce the cost of capital. Moreover, in making decisions whether to retain or transfer risks, companies should generally be guided by the principle of comparative advantage. If an outside firm or investor is willing to bear a particular risk at a lower price than the cost to the firm of managing that risk internally, then it makes sense to lay off that risk. Along with the greater efficiency and return on capital promised by such an approach, several panelists also pointed to one less tangible benefit of an enterprise‐wide risk management program—a significant improvement in the internal corporate dialogue, leading to a better understanding of all the company's risks and how they are affected by the interactions among its business units.